Peningkatan Pengetahuan Kesehatan Gigi dan Mulut pada Remaja: Siswa SMP St. Bellaminus Menteng Jakarta - Ferry Sandra; Komariah Komariah; Wiena Widyastuti; Muhammad Novo Perwira Lubis; Bianda Claresta; Joceline Setiawan; Steward Steward; Maria Verena Emeralda; Louise Anastasya (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
This community health service aims to educate and to train St. Bellarminus Junior High School Students on the importance of dental and oral health for adolescents. The community health service program was initialized with situational analysis. Students' prior knowledge (pre-test) was assessed with 16 questions using Google form on 61 students. For the intervention, education and training was performed virtually. After the intervention, post-test was conducted to evaluate the effectiveness. Pre- and post-test questions were divided in 3 categories, which were A: general health, B: dental and oral health, C: advanced dental and oral health. Based on the pre- and post-test results, the community service program had increased the numbers of students answering correctly for each question. The percentage of students answering correctly was elevated from 57.58% (pre-test results) to 72.23% (post-test results). Meanwhile, based on knowledge category, the A and B categories were both markedly elevated after the program, suggesting the program has given positive impact for the St. Bellarminus Junior High students. Since the community health service program has given positive impact for students, hence the program should be conducted continuously.